LOVE AND DO WHAT YOU WANT: SOME NOTES ON SAINT AUGUSTINE’S ETHICS - de Contaldo, Sílvia Maria (2022)
The article aims to propose a reflection on the Augustinian ethical principle “Love and Do what you want” and its correlations with ethics, the realm of human actions. Often repeated and often misunderstood or misinterpreted, Augustine's exhortation, found in his Commentary on the First Letter of John (VII, 8), can be a starting point for deepening the knowledge and debate on the ethical values that are at stake in the contemporary world.